Consumer Acceptability and Attitude towards Organic Food Products with reference to Health Perception and Sustainable Choices - S. Varshini,; Dr. J. Josephine Daisy, (IJRDO - Journal of Business Management, 2025)
The rising awareness of health and sustainability has reshaped consumer preferences in the food sector where organic products have gained strong relevance. The study aims to examine how health perception and sustainability awareness influence consumer attitude and purchasing behaviour toward organic food products. An empirical research design was adopted since it enables direct observation of consumer patterns and provides measurable insight into their behavioural tendencies. Primary data were collected through a structured questionnaire designed around three constructs: health perception, sustainability awareness, and consumer attitude. The target population included active consumers of organic food in the urban areas of Salem city where the market has shown consistent expansion. The final dataset consisted of 301 valid responses selected through statistical justification using Cochran’s formula. Analytical techniques such as factor analysis, cluster analysis, and MANOVA were employed to identify latent constructs, classify behavioural segments, and assess multivariate differences among consumer groups. The findings revealed that health perception significantly shapes attitude toward organic products and that sustainability awareness strengthens this association by reinforcing ethical and responsible buying patterns. The results also indicated that both factors jointly influence purchase behaviour, demonstrating that consumer decisions in the organic market stem from both self-oriented health motives and socially oriented sustainability considerations. The study contributes to understanding the psychological and ethical bases of organic consumption, offering insights for marketers and policymakers to design strategies that align with consumers’ values and promote sustainable purchasing behaviour.